Ammonia volatilization and pasture yield of Urochloa decumbens fertilized with nitrogen sources - Meirelles, Guilherme Constantino [UNESP]; Heinrichs, Reges [UNESP]; Lira, Maikon [UNESP]; Ribeiro Virgílio, Igor [UNESP]; Felipe Melo dos Santos, Luis [UNESP]; Bonfim Cassimiro, Juliana [UNESP]; Luis Ruffo, Matias; Viega Soares Filho, Cecilio; Moreira, Adônis (Taylor & Francis, 2022)
Tropical pastures show a response to nitrogen (N) fertilization is challenging due to ammonia volatilization (AV) loss when applied on the soil surface and the impossibility of incorporating the fertilizer. The objective of this study was to evaluate AV loss and shoot dry weight yield (SDWY) of Urochloa decumbens over two growing seasons. The urea, ammonium nitrate (AN), and urea treated with urease inhibitor (U+NBPT) at three N rates (0 [control], 100 and 200 kg ha-1 N) applications were evaluated. Urea resulted in the largest AV losses and increased of 200 kg ha-1 N. Conversely, the largest SDWY was obtained with AN and U+NBPT, which did not differ, in comparison to urea that resulted in the lowest SDWY among the N sources. The increase of N rate resulted in the largest SDWY. The deleterious effect of AV loss on SDWY was more pronounced for the 100 kg ha-1 N due to a more limited N supply. These results show that the N and AV loss significantly decrease of SDWY in U. decumbens pasture. The use of NBPT treated urea is a viable technology to increase pasture productivity and minimize AV losses on established pastures under tropical conditions. .
Keywords: ammonia volatilization; NBPT urease inhibitor; Pasture productivity